2014
DOI: 10.1098/rspb.2014.1806
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body condition influences magnitude of anti-predator response in offspring

Abstract: Organisms exhibit plasticity in response to their environment, but there is large variation even within populations in the expression and magnitude of response. Maternal influence alters offspring survival through size advantages in growth and development. However, the relationship between maternal influence and variation in plasticity in response to predation risk is unknown. We hypothesized that variation in the magnitude of plastic responses between families is at least partly due to maternal provisioning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Fox & Czesak 2000;Hendry et al 2001) and has longterm effects on their growth and fitness (Roff 1992). Recent studies have suggested that maternal provisioning impacts plasticity in offspring defences and predator avoidance behaviours (Michimae et al 2009;Bennett & Murray 2014). For example, in the northern leopard frog (Lithobates pipiens), mothers in better body condition, who produced larger eggs, had tadpoles that developed greater morphological responses to predation risk (Bennett & Murray 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fox & Czesak 2000;Hendry et al 2001) and has longterm effects on their growth and fitness (Roff 1992). Recent studies have suggested that maternal provisioning impacts plasticity in offspring defences and predator avoidance behaviours (Michimae et al 2009;Bennett & Murray 2014). For example, in the northern leopard frog (Lithobates pipiens), mothers in better body condition, who produced larger eggs, had tadpoles that developed greater morphological responses to predation risk (Bennett & Murray 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that maternal provisioning impacts plasticity in offspring defences and predator avoidance behaviours (Michimae et al 2009;Bennett & Murray 2014). For example, in the northern leopard frog (Lithobates pipiens), mothers in better body condition, who produced larger eggs, had tadpoles that developed greater morphological responses to predation risk (Bennett & Murray 2014). Importantly, in most taxa, the extent of maternal investment is adjusted plastically, as an adaptive response to local environmental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals can also respond by not breeding or by reducing their energy expenditure through reduced offspring numbers, offspring size and parental care, which leads to reduced offspring survival (Mousseau & Fox, 1998;Karell et al, 2008;Rode et al, 2010;Johnson et al, 2014). Maternal condition can also influence offspring survival through the transfer of maternal hormones, antibodies or other substances (Karell et al, 2008;Bennett & Murray, 2014;Bergman et al, 2014) and therefore shows carry-over effects to future generations (Van Allen et al, 2010). However, individuals sometimes increase their reproductive effort as a terminal investment to maintain their breeding output, but may die of exhaustion after reproduction is complete (Clutton-Brock, 1984).…”
Section: Figmentioning
confidence: 99%
“…Specifically, we first estimate the contributions of maternal effects (V M ), relative to that of additive genetic (V A ) and environmental effects (V E ), for larval responses to predation risk. Second, we test if larval responses to predation risk –which are known to depend on the larva’s initial size–, are influenced by variation in maternal or paternal body size, a key trait known to impact offspring phenotype in many systems (Fox 1994; Bernardo 1996 a ; Fox and Czesak 2000; Bennett and Murray 2014). Finally, we estimate the relative contribution of additive genetic and environmental variances (V A and V E ) of maternal responses to predation risk, including changes in intraclutch cannibalism –a mechanism linked to an anticipatory maternal effect.…”
Section: Introductionmentioning
confidence: 99%